The Analysis of Listening Anxiety of Advanced Listening Class Students of English Department in Universitas Negeri Padang - Amalya Shawfani; Aryuliva Adnan; Leni Marlina (Universitas Negeri Padang, 2020)
Plenty of students in Department of English in Universitas Negeri Padang have experience of anxiety in advanced listening classes. Based on the observation, related with the anxiety during the listening class, they cannot comprehend the listening very well and it results toward listening anxiety. As a result, every time listening class begins; most students tend to have perspective that they cannot do the listening practice due to their anxiety. That is why this research needs to be conducted. The aim of this research was to analyse the listening anxiety of the students in Advanced Listening class of English Department. This research used qualitative research and the population was from all the students who were having Advanced Listening class. The sampling of this research was purposive sampling by using sample 50 students from class K1-K5 in batch 2018 that took advanced listening class. The data were collected through questionnaire and interview. This result of this showed that the students’ anxiety resulted from the students’ factor and had high anxiety level when they were in the advanced listening class and there were two other factors that caused the listening anxiety. They were listening material and lecturers’ factor. So, it is known that no matter the level of listening skill they are in, the students still keep the high level of listening anxiety.